RETRACTED: Exploring the Asymmetric Impact of Public Debt on Renewable Energy Consumption Behavior - Jianhua, Luo (Frontiers in Psychology, 2022)
The mounting pollution burden has raised the need for renewable energy demand throughout the world. The study aims to explore the effect of public debt on renewable energy consumption for selected 23 Asian economies for the time period 1990-2019. Long-run empirical findings of the group-wise symmetric ARDL model reveal that increasing public debt results in declining renewable energy consumption. However, findings of the long-run group-wise asymmetric ARDL model reveal that positive shock in public debt reduces renewable energy consumption, and negative shock in public debt results in increasing renewable energy consumption. The economy-wise empirical findings of the FMOLS model reveal that an increase in public debt results in increased renewable energy consumption in nine economies and decreased renewable energy consumption in six economies. The asymmetric FMOLS findings reveal that positive shock in public debt increases renewable energy consumption in nine economies and also decreases renewable energy consumption in nine economies. However, a negative shock in public debt increases renewable energy consumption in 12 economies and decreases renewable energy consumption in 5 economies. Additionally, this research provides numerous policy implications for renewable energy sources in Asian economies.